Volume Guarantee High-Frequency Oscillatory Ventilation in Preterm Infants With RDS: Tidal Volume and DCO2 Levels for Optimal Ventilation Using Open-Lung Strategies - Tuzun, Funda; Deliloglu, Burak; Cengiz, Merve Meryem; Iscan, Burcin; Duman, Nuray; Ozkan, Hasan (Frontiers in Pediatrics, 2020)
High frequency oscillatory ventilation with volume-guarantee (HFOV-VG) is a promising lung protective ventilator mode for the treatment of respiratory failure in newborns. However, indicators of optimal ventilation during HFOV-VG mode are not identified yet. In this study, we aimed to evaluate optimal high-frequency tidal volume (VThf) and the dissociation coefficient of CO2 (DCO2) levels to achieve normocapnia during HFOV-VG after lung recruitment in very low birthweight infants with respiratory distress syndrome (RDS). Preterm babies under the 32nd postmenstrual week with severe RDS that received HFOV-VG using open-lung strategy between January 2014 and January 2019 were retrospectively evaluated. All included patients were treated with the Dräger Babylog VN500 ventilator in the HFOV-VG mode. In total, 53 infants with a mean gestational age of 26.8±2.3 weeks were evaluated. HFOV mean optimal airway pressure (MAPhf) level after lung recruitment was found to be 10.2±1.7 mbar. Overall, the mean applied VThf per kg was 1.64 0.25 mL/kg in the study sample. To provide normocapnia, the mean VThf was 1.61±0.25 mL/kg and the mean DCO2corr was 29.84±7.88 mL/kg2/sec. No significant correlation was found between pCO2 levels with VThf (per kg) or DCO2corr levels. VThf levels to maintain normocarbia were significantly lower with 12 Hz frequency compared to 10 Hz frequency (1.50± 0.24 mL /kg vs 1.65± 0.25 mL/ kg, p< 0.001, respectively). A weak but significant positive correlation was found between mean airway pressure (MAPhf) and VThf levels. To our knowledge, this is the largest study to evaluate the optimal HFOV-VG settings in premature infants with RDS, using the open-lung strategy. According to the results, a specific set of numbers could not be recommended to achieve normocarbia. Following the trend of each patient and small adjustments according to the closely monitored pCO2 levels seems logical.